Dynamical interactions between Loop Current and Loop Current Frontal Eddies in a HYCOM ensemble of the circulation in the Gulf of Mexico - Yang, Xingchen; Le Hénaff, Matthieu; Mapes, Brian; Iskandarani, Mohamed (Frontiers in Marine Science, 2023)
The dynamics of the Loop Current (LC) system prior to Eddy Franklin detachment in 2010 is investigated using an ensemble of simulations where the strength and size of a West Florida Shelf Cyclonic Eddy (WFCE) are perturbed.Ensemble members with in the Gulf of Mexico (GoM), specifically during the shedding of Eddy Franklin in 2010, is investigated using an ensemble of simulations. The ensemble members differed in their initial conditions of the Florida Shelf Cyclonic Eddy (WFCE), which in turn significantly influences the timing and occurrence of the Loop Current Eddy (LCE) detachment. The results reveal that a stronger and larger WFCE lead leads to an early LCE detachment, while members with a weaker and smaller WFCE result results in late or even no detachment during the sixty days of the within the 60-day simulation period. The initial WFCE's size and strength of the initial WFCE are also found to impact the evolution of Campeche Bank Cyclonic Eddies (CBCE). When a large and strong WFCE intrudes into the LC, potential vorticity (PV) over the eastern Campeche Bank (CB) grows fast and a CBCE is prone to form, as was ⋆ Fully documented templates are available in the elsarticle package on CTAN.